The construction of legal basis relevant to the state of law in the event of pandemic emergency: a lesson from Indonesia - Widiarto, Aan Eko; Dahlan, Muhammad; Arrsa, Ria Casmi (Faculty of Law, University of Muhammadiyah Malang, 2022)
This paper aims to study the construction of an appropriate legal basis for a state of law in responding to the Covid-19 emergency. As a state of law, Indonesia has been making many regulations at both central and local government levels. The regulations vary, ranging from Government Regulations in Lieu of Law, Ministerial Regulations, Ministerial Decrees, and Joint Decrees of Ministerial Instructions, to the Regulations of Regional Heads, and these regulations have led to overlapping regulations. With normative-juridical methods, the prescriptive technique was used to further analyze the problem and find a new concept of the construction of an appropriate legal basis in responding to the Covid-19 emergency. The research results show that, juridically, the use of non-legal products such as Ministerial Instructions and Circular Letters issued by ministers during the Covid-19 emergency in Indonesia has fulfilled the procedural aspects of law-making but not the substantive ones regarding the curbs restricting people’s social activities. This research recommends that the construction of a legal basis intended to respond to a state of emergency should simultaneously meet both procedural and substantive aspects